Recent therapeutic approaches to cystathionine beta-synthase-deficient homocystinuria - Majtan, Tomas; Kožich, Viktor; Kruger, Warren D (British journal of pharmacology, 2023)
Cystathionine beta-synthase (CBS)-deficient homocystinuria (HCU) is the most common inborn error of sulfur amino acid metabolism. The pyridoxine non-responsive form of the disease manifests itself by massively increasing plasma and tissue concentrations of homocysteine, a toxic intermediate of methionine metabolism that is thought to be the major cause of clinical complications including skeletal deformities, connective tissue defects, thromboembolism and cognitive impairment. The current standard of care involves significant dietary interventions that, despite being effective, often adversely affect quality of life of HCU patients, leading to poor adherence to therapy and inadequate biochemical control with clinical complications. In recent years, the unmet need for better therapeutic options has resulted in development of novel enzyme and gene therapies and exploration of pharmacological approaches to rescue CBS folding defects caused by missense pathogenic mutations. Here, we review scientific evidence and current state of affairs in development of recent approaches to treat HCU.
Keywords: Mutation, Missense; gene therapy; cystathionin-beta-synthasa; kvalita života; Cystathionine beta-Synthase; missense mutace; Quality of Life; Thromboembolism; pegtibatinase; homocystinuria; proteasome inhibitors; lidé; Humans; cystathionine beta-synthase; homocystinurie; chaperones; tromboembolie; Homocystinuria; enzyme therapy